2020
DOI: 10.1111/aas.13671
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxemia following hospital discharge after fast‐track hip and knee arthroplasty – A prospective observational study subanalysis

Abstract: The study was supported by a grand from the Lundbeck Foundation, Hellerup Denmark. The foundation is independent of the pharmaceutical company Lundbeck and was not involved in designing or conducting the study. Background: Post-operative hypoxemia is prevalent in hospitalized patients and may adversely affect recovery. However, little data exist on the post-discharge phase or details on duration, severity and potential risk factors. Thus, we investigated the incidence and risk factors for severe desaturation d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Lung lesions, post-traumatic pulmonary micro thromboembolism, fat embolism syndrome, and damage-associated molecular patterns may contribute to preoperative hypoxaemia ( 11 ). In this study, we found that preoperative hypoxaemia was an independent risk factor for postoperative hypoxaemia, which was consistent with the findings of Luna et al ( 30 ). In their study, preoperative hypoxaemia significantly increased the risk of postoperative hypoxaemic events during the first week in patients undergoing joint replacement.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lung lesions, post-traumatic pulmonary micro thromboembolism, fat embolism syndrome, and damage-associated molecular patterns may contribute to preoperative hypoxaemia ( 11 ). In this study, we found that preoperative hypoxaemia was an independent risk factor for postoperative hypoxaemia, which was consistent with the findings of Luna et al ( 30 ). In their study, preoperative hypoxaemia significantly increased the risk of postoperative hypoxaemic events during the first week in patients undergoing joint replacement.…”
Section: Discussionsupporting
confidence: 93%
“…Lung lesions, post-traumatic pulmonary micro thromboembolism, fat embolism syndrome, and damage-associated molecular patterns may contribute to preoperative hypoxaemia (11). In this study, we found that preoperative hypoxaemia was an independent risk factor for postoperative hypoxaemia, which was consistent with the findings of Luna et al (30).…”
Section: Risk Factors For Postoperative Hypoxaemiasupporting
confidence: 93%
See 1 more Smart Citation
“…We choose to carry out APP treatment for the first three consecutive PODs to prevent PPCs for the following reasons: 1. The peak time for diagnosis of PPCs and hypoxemia occurred on POD 4 after hip fracture surgery in the elderly [ 10 , 55 ]. 2.…”
Section: Discussionmentioning
confidence: 99%